The Impact of Educator Quality on Graduate Competence and Quality - Joned Ceilendra Saksana; Asep Surya Lesmana; Siskamto; Sri Murtini; Zubair Arza (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This paper aims to explore and discuss the crucial impact of educator quality and competence on producing high-quality graduates by examining relevant literature and its application in existing research. Employing a qualitative methodology, including systematic literature review and content analysis, the study draws from literature sourced online concerning the variables under investigation. The analysis incorporates insights from fifteen scholarly articles, shedding light on the relationship between the quality of educators and graduates. Findings indicate that existing literature has been effectively integrated into the study's conclusions. The recommendations provided offer qualitative contributions to the field of education, particularly in education management. Future research can build on this work by examining the same variables using different methods and research contexts